Photodynamic therapy applications – review - Maciej Michalak; Sandra Mazurkiewicz; Jakub Szymczyk; Daniel Ziental; Łukasz Sobotta (Journal of Medical Science, 2023)
Photodynamic therapy (PDT) is getting attention treatment method all over the world. As it is overviewed in the article among others strategies this technique is useful in the treatment of diseases in a wide range of disciplines: dermatology, urology, gynecology, as well as head and neck cancers and age-related macular degeneration. Recently, the development of this method is focused on looking for new photosensitizers and optimizing the dosimetry. Current articles report that PDT in many cases is a significant supply of the conventional treatment protocols but more than once it can be used as a method of choice, providing excellent outcomes and low after treatment stress on the patient.